Forecasting performance of wavelet neural networks and other neural network topologies: A comparative study based on financial market data sets - Markus Vogl; Peter Gordon Rötzel, LL.M; Stefan Homes (Machine Learning with Applications, 2022)
In this study, we analyse the advantageous effects of neural networks in combination with wavelet functions on the performance of financial market predictions. We implement different approaches in multiple experiments and test their predictive abilities with different financial time series. We demonstrate experimentally that both wavelet neural networks and neural networks with data pre-processed by wavelets outperform classical network topologies. However, the precision of conducted forecasts implementing neural network algorithms still propose potential for further refinement and enhancement. Hence, we discuss our findings, comparisons with “buy-and-hold” strategies and ethical considerations critically and elaborate on future prospects.